2015
DOI: 10.1021/acsnano.5b04583
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific and Size-Dependent Ag Nanoparticle Toxicity in Gills and Intestines of Adult Zebrafish

Abstract: We studied adult zebrafish to determine whether the size of 20 and 110 nm citrate-coated silver nanoparticles (AgC NPs) differentially impact the gills and intestines, known target organs for Ag toxicity in fish. Following exposure for 4 h, 4 days, or 4 days plus a 7 day depuration period, we obtained different toxicokinetic profiles for different particle sizes, as determined by Ag content of the tissues. Ionic AgNO3 served as a positive control. The gills showed a significantly higher Ag content for the 20 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(93 citation statements)
references
References 45 publications
5
84
0
4
Order By: Relevance
“…[19][20][21] The cytotoxicity of AgNPs could be influenced by particle size, surface-stabilizing agents, pH, and some other factors. 1,5,7,[22][23][24] The surface-stabilizing coating is one of the most important factors for protecting cell viability from AgNPs. [25][26][27] Previous studies have shown that chitosan has a very good biocompatibility and antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] The cytotoxicity of AgNPs could be influenced by particle size, surface-stabilizing agents, pH, and some other factors. 1,5,7,[22][23][24] The surface-stabilizing coating is one of the most important factors for protecting cell viability from AgNPs. [25][26][27] Previous studies have shown that chitosan has a very good biocompatibility and antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…Far than chemical composition, size and shape are crucial factors determining the relationships between nanoparticles and increasingly complex biological systems (namely from cells to entire organisms) in critical aspects such as organ specificity and biodistribution [36][37][38][39][40], toxicity [41], and cell uptake and fate [39,[42][43][44][45]. Although previously checked in several types of nanostructures, mainly in crystalline nano-and micromaterials, the present study is the first evaluation of form (geometry) and function (cellular uptake) of protein nanoparticle populations.…”
Section: Discussionmentioning
confidence: 99%
“…The 20 nm Ag ENPs gained access to the basolateral membrane, whereas both 110 nm Ag ENPs and the ions were confined to the apical membrane 122. Differences were also observed in gill tissue, where Ag ENPs were mainly located on the secondary filaments, whereas Ag was mostly present in the primary filaments of zebrafish exposed to the ionic control 122. This highlights the need to account for differences in the internalization and translocation on the basis of the size of ENPs and also compared to a dissolved control.…”
Section: Uptake Internalization and Translocation Of Engineered Namentioning
confidence: 99%